The selection of ministers around the world - Dowding, Keith M. (Routledge research on social and political elites, 2015)
This book examines the process of selection, shuffling and removal of ministers in national cabinets around the world. Drawing on original data over several decades, it offers a series of case studies of countries from around the world with differing institutional and cultural structures including presidential and semi-presidential systems, and parliamentary, unitary and federal systems, some of which have experienced periods under authoritarian regimes. Featuring 14 case studies on North and South America, Asia, Africa, Australia and New Zealand, this book complements the earlier volume The Selection of Ministers in Europe (Routledge, 2009).